Risk factors for the development of cervical cancer: analysis of the evidence - Luvián-Morales, Julissa; Gutiérrez-Enríquez, Sandra Olimpia; Granados-García, Víctor; Torres-Poveda, Kirvis (Frontiers in Oncology, 2024)
Introduction. Cervical cancer (CC) is the fourth most prevalent female cancer globally. Understanding its epidemiology is crucial for devising practical strategies suited to geographic and social contexts to attain the global eradication of CC. Hence, this study examined the latest evidence of risk factors contributing to CC development. Methods. An independent literature search was conducted on PubMed using MESH terms. The primary sources were meta-analyses published from 2010 to 2023, which detail updated evidence on risk factors associated with CC. Additionally, the quality of the evidence was evaluated using the GRADE system and recommendations were made accordingly. Results. The main risk factors related to the cause of CC include co-infections with other sexually transmitted infections, genetic markers, cervicovaginal microbiota, nutritional factors, comorbidities that affect the immune response, smoking, and the use of hormonal contraceptives with a quality evidence based on the GRADE scale moderate. Conclusions. Since the necessary cause for CC is persistent cervicovaginal HPV, all the risk factors implicated in the causality of CC act as non-independent cofactors that increase the risk of CC. Thus, changes in public policies aimed at addressing these risk factors are highly recommended and can substantially decrease the risk of CC.